Answer:
-2x-6 I think
Step-by-step explanation:
I think that it is -2x-6 because I did -2 and x is -2x and -2 times -3 is 6.
Answer:
x = 9
y = 3
Step-by-step explanation:
2x + 2y = 24 is the same as x + y = 12
using substitution, x = 12-y
12 - y = 3y
12 = 4y
y = 3
x = 3(3)
x = 9
Answer:
Kim will need to spend 67 minutes on her sixth ride
Step-by-step explanation:
Represent the number of minutes of her sixth ride by m.
Then the average number of minutes is
53 + 43 + 56 + 54 + 45 + m
---------------------------------------- = 53
6
Multiplying both sides of this equation by 6 yields
6(53 + 43 + 56 + 54 + 45 + m)
--------------------------------------------- = 6(53)
6
which simplifies to
251 + m
---------------- = 318
or 251 + m = 318. Subtract 251 from both sides to obtain the value of m:
m = 318 - 251 = 67
Kim will need to spend 67 minutes on her sixth ride to attain an average ride length of 53 minutes.i
Answer:
y = -17/2
Step-by-step explanation:
Substitute with the givens.
30= 8(8) + 4y.
Multiply parentheses.
30 = 64 + 4y
Subtract.
30-64= -34
-34 = 4y.
Divide each side by 4.
y = - 8.5, or -17/2
hope that is right!
When you divide it in a calculator it comes out to 19.6. Can u pls paste the answers here?